2022
DOI: 10.1161/circresaha.121.320680
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy With the N-Terminus of Junctophilin-2 Improves Heart Failure in Mice

Abstract: Background: Transcriptional remodeling is known to contribute to heart failure (HF). Targeting stress-dependent gene expression mechanisms may represent a clinically relevant gene therapy option. We recently uncovered a salutary mechanism in the heart whereby JP2 (junctophilin-2), an essential component of the excitation-contraction coupling apparatus, is site-specifically cleaved and releases an N-terminal fragment (JP2NT [N-terminal fragment of JP2]) that translocates into the nucleus and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Thus, the current study reveals an unappreciated role of JPH2 in preventing cardiomyocyte apoptosis under stress; and our data together with previous findings suggest that targeting JPH2 may be a useful therapeutic strategy to reduce cardiac pathology under stress. Indeed, transgenic over-expressionof JPH2 or its N-terminus,and gene therapy with its N-terminus attenuate myocardial remodeling and dysfunction in pre-clinical mouse models of heart failure 12, 16, 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current study reveals an unappreciated role of JPH2 in preventing cardiomyocyte apoptosis under stress; and our data together with previous findings suggest that targeting JPH2 may be a useful therapeutic strategy to reduce cardiac pathology under stress. Indeed, transgenic over-expressionof JPH2 or its N-terminus,and gene therapy with its N-terminus attenuate myocardial remodeling and dysfunction in pre-clinical mouse models of heart failure 12, 16, 44 .…”
Section: Discussionmentioning
confidence: 99%
“…While in CUPID phase 1/2a clinical trial, the safety of AAV1/SERCA2a for advanced HF was confirmed to be good, and the body (81). A recent study demonstrated that AAV-JP2NT entry into the myocardium attenuated HF development and stressinduced transcriptional remodeling (110).…”
Section: Raav Vector Was Used For Gene Therapy In Heart Failure Modelmentioning
confidence: 99%
“…In this issue, Wang et al 6 describe an approach that may bridge the two approaches through the singular behavior of the structural protein JPH-2 (junctophillin 2).…”
Section: Article See P 1306mentioning
confidence: 99%
“…Wang et al 6 have demonstrated that mice overexpressing JPH-2NT have a significantly milder cardiac phenotype following the induction of cardiac hypertrophy following transverse aortic constriction (TAC). The hearts of mice overexpressing JPH-2NT display much less fibrosis and a preserved cellular TAT network.…”
mentioning
confidence: 99%